A comparative study of oral versus intravenous iron in the treatment of moderately anaemic pregnant women - Gupta, Shivika; Gupta, Ranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Anemia, the decrease of haemoglobin (Hb) concentration is a common disorder complicating pregnancy mostly due to hemodilution, increased demand of iron and poor dietary intake of iron. The aim of this study was to evaluate whether parenteral iron sucrose can be used as an alternative to daily oral iron during pregnancy. Methods: It was a prospective interventional study conducted in the Department of Obstetrics and Gynaecology, Rohilkhand Medical College and Hospital, Bareilly involving pregnant women at 16-24 weeks with Hb 7-10 g/dl. They were randomly allocated to two groups I and II. Group I (oral group) was given oral iron tablets containing 100 mg of elemental iron and 0.5 mg of folic acid as per therapeutic requirement. Group II (parenteral group) were admitted as day care patients and given a total calculated dose of iron sucrose in divided doses of 200 mg each in 100 ml of normal saline as slow intravenous infusion. Hb, packed cell volume (PCV), blood indices were measured at the start, 2 weeks and 4 weeks of treatment. Any side-effects of treatment were also studied. Results: A statistically significant increase in values of Hb, hematocrit, reticulocyte count, red blood cells (RBC’s) indices: mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) and mean corpuscular hemoglobin (MCH) coupled with no serious side effects with iron sucrose as compared with oral iron. Conclusions: Intravenous iron sucrose complex is safe, convenient and effective alternative to oral iron for treatment of iron deficiency anemia in pregnancy.